Analysis of Single Nucleotide Polymorphisms and Radiation Sensitivity of the Lung Assessed With an Objective Radiologic Endpoint - Kelsey, Chris R. (2013)
To explore the possibility that underlying genetic susceptibility influences radiation-induced lung injury, we studied pulmonary damage after radiation therapy for lung cancer and single nucleotide polymorphisms implicated in radiation sensitivity. An objective radiologic method (perfusion single photon emission computed tomography) was used to assess radiation sensitivity. An association between single nucleotide polymorphisms in XRCC1 and BRCA1 and radiation sensitivity of the lungs was noted. BACKGROUND: The primary objective of this study was to evaluate the association between radiation sensitivity of the lungs and candidate single nucleotide polymorphisms (SNP) in genes implicated in radiation-induced toxicity. METHODS: Patients with lung cancer who received radiation therapy (RT) had pre-RT and serial post-RT single photon emission computed tomography (SPECT) lung perfusion scans. RT-induced changes in regional perfusion were related to regional dose, which generated patient-specific dose-response curves (DRC). The slope of the DRC is independent of total dose and the irradiated volume, and is taken as a reflection of the patient’s inherent sensitivity to RT. DNA was extracted from blood samples obtained at baseline. SNPs were determined by using a combination of high-resolution melting, TaqMan assays, and direct sequencing. Genotypes from 33 SNPs in 22 genes were compared against the slope of the DRC by using the Kruskal-Wallis test for ordered alternatives. RESULTS: Thirty-nine self-reported Caucasian patients with pre-RT and ≥6 month post-RT SPECTs, and blood samples were identified. An association between genotype and increasing slope of the DRC was noted in G(1301) A in XRCC1 (rs25487) (P = .01) and G(3748) A in BRCA1 (rs16942) (P = .03). CONCLUSIONS: By using an objective radiologic assessment, polymorphisms within genes involved in repair of DNA damage (XRCC1 and BRCA1) were associated with radiation sensitivity of the lungs.